PET-Health Interprofessionality and the readiness of students for interprofessional learning - Marques, Juliana Ferreira Lima; Costa, Marcelo Viana da (Saúde e Sociedade, 2023)
Interprofessionality was the central theme of the ninth call for proposals of the Education by Working for Health Program. The objective of this study was to describe the readiness of students who participated in the program for interprofessional learning. The research, of a quantitative approach and descriptive-exploratory perspective, collected data by applying the readiness for interprofessional learning scale (RIPLS), adapted for Brazilian Portuguese. The results indicate an important readiness for teamwork and collaboration. Relevant percentages were also found regarding professional identity, indicating good readiness for interprofessional learning, although aspects related to competition appeared in lower percentages of agreement regarding shared learning and interdependence of professional practices. For user-centered care, results were also found indicating good readiness among participants; however, aspects related to the collaboration of the user in the production of health services still express the tendency of a professional-centered logic. In conclusion, there is a positive readiness for interprofessional education, which needs to be increasingly stimulated in policies and strategies of curricular reforms.